2021
DOI: 10.17159/2309-8775/2021/v63n4a3
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of South African low-income housing roof anchor systems

Abstract: The current roof anchoring methods for houses in South Africa are described in the standard SANS 10400. The adequacy of these prescribed roof anchoring methods for low-income houses (LIHs) is questionable, due to several recently reported failures caused by strong winds. This study quantitively investigates the performance of the prescribed roof anchoring methods through numerical methods, and focuses on LIHs with light-weight roofs supported on single-leaf masonry walls. The masonry walls comprise either soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a study assessing the performance of deemed-to-satisfy SANS 10400 masonry wall provisions, de Villiers et al (2021) concluded that the wall provisions require reconsideration to align with current South African loading conditions. In another study assessing the performance of deemed-to-satisfy SANS 10400 roof anchor systems, Van Der Merwe & Mahachi (2021) suggested the revision of the deemed-to-satisfy provisions in accordance with the criteria that is suitable for the current climate conditions.…”
Section: Development Of South African Structural Performance Criteria...mentioning
confidence: 99%
“…In a study assessing the performance of deemed-to-satisfy SANS 10400 masonry wall provisions, de Villiers et al (2021) concluded that the wall provisions require reconsideration to align with current South African loading conditions. In another study assessing the performance of deemed-to-satisfy SANS 10400 roof anchor systems, Van Der Merwe & Mahachi (2021) suggested the revision of the deemed-to-satisfy provisions in accordance with the criteria that is suitable for the current climate conditions.…”
Section: Development Of South African Structural Performance Criteria...mentioning
confidence: 99%